Management of a pregnancy complicated by type III spinal muscular atrophy. (18th February 2011) - Howarth, L; Glanville, T
Abstract : The authors report the successful management of a pregnancy in a patient with spinal muscular atrophy (SMA) type III. It is a genetically inherited condition causing increasing weakness of the skeletal muscle. The patient in our case was confined to a wheelchair due to marked weakness in her lower limbs. A review of the available literature identified potential risk factors for the antenatal, intrapartum and postpartum period. These include increased risk of thromboembolism, urinary tract infections, intrauterine growth restriction and preterm delivery, anaesthetic problems and increased risk of uterine atony with subsequent postpartum haemorrhage. The authors report the management of these risk factors and the reasons for delivery by Caesarean section at 32 weeks. Apart from a decline in muscle function postdelivery requiring physiotherapy, there were no adverse outcomes for mother or baby. In both this case and on review of the literature, it is proven that a successful pregnancy is possible with SMA.